CLINICIAN SENSITIZATION ON INTEGRATED DISEASE SURVEILLANCE AND RESPONSE IN FEDERAL MEDICAL CENTRE OWO, ONDO STATE, NIGERIA, 2016 - Ilesanmi, Olayinka Stephen; Babasola, Oluwafolakemi Mary (Public Health of Indonesia, 2017)
Background: For effective Integrated Disease Surveillance and Response (IDSR) all health care workers involvement is required. Most trainings have often neglected the clinicians. Aim: This study aimed to identify gaps requiring capacity building in preventing infectious disease outbreak among health care workers in Federal Medical Centre, Owo, Ondo State.Methods: A cross sectional study of clinicians at the Federal Medical Centre, Owo was done. Data was collected using semi structured interviewer administered questionnaire. Data collected were analysed with SPSS version 21. Summary statistics was conducted to identify training need requirements.Results: The mean age of participant was 43 ± 5.9 years, 14(70%) were male. Respondents who have worked for 10 years and above were 12(60%). In all, 5(25%) respondent understood disease surveillance to be systematic collection of data and analysis in order to prevent diseases. Regarding respondent's knowledge of notifiable diseases. Only 4(20%) of the respondents knew malaria as a notifiable disease, Cholera knew by 11(55%), Ebola by 15(75%) and Lassa by 13(65%). The main factor identified to be affecting prompt disease notification in  Federal Medical Centre,  Owo was lack of adequate training 12(60%) while communication gap was identified by 7(35%). In all, 18(90%) felt they do not know all that they needed about disease surveillance. Conclusion: Rapid notification of infectious diseases is essential for prompt public health action and for monitoring of disease trends. Trainings that will improve the level of knowledge of clinician and communication channels will improve disease surveillance and notification.